Effects of Angular Fillers on Thermal Runaway of Lithium-Ion Battery. Issue 11 (November 2016) - Wang, Meng; Le, Anh V.; Shi, Yang; Noelle, Daniel J.; Yoon, Hyojung; Zhang, Minghao; Meng, Y. Shirley; Qiao, Yu
Abstract : By adding 1 wt% damage homogenizer (DH), i.e. carbon black microparticles, into the electrodes of lithium-ion batteries, thermal runaway can be mitigated as the battery cells are subjected to impact loadings. In a drop tower test, the generated heat of the modified cells is reduced by nearly 40%, compared with the reference cells. This phenomenon may be attributed to the weakening effect of the carbon black fillers. The shape of the filler grains does not have a pronounced influence on the temperature profile.